Legal Weaknesses in Enforcing Good Governance Principles in Licensing Corruption: Kelemahan Penegakan Hukum Asas Pemerintahan yang Baik dalam Korupsi Perizinan - Jhon Elvis Situmeang; Rizki Jutarido Zahri; Arfiansyah Arfiansyah (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The General Principles of Good Governance constitute fundamental norms in state administrative law that guide the legality of governmental actions. Specific Background: In Indonesia’s licensing administration, these principles are formally regulated to ensure legal certainty, transparency, accountability, and public interest, yet licensing practices frequently deviate through abuse of authority and corruption cases. Knowledge Gap: Existing enforcement mechanisms tend to prioritize criminal prosecution without first addressing administrative violations, resulting in weak integration between administrative law and criminal law. Aims: This study aims to analyze juridically the enforcement of Good Governance Principles in licensing corruption cases and to clarify the proper qualification of such violations within the administrative law framework. Results: The findings demonstrate that violations of Good Governance Principles in licensing constitute abuse of authority that should be initially addressed as administrative violations before criminal proceedings, in order to ensure legal coherence. Novelty: This study emphasizes the juridical positioning of administrative sanctions as a preliminary mechanism prior to criminal liability in licensing corruption cases. Implications: Strengthening regulations, internal supervision by governmental auditors, the role of the Ombudsman, and licensing digitalization is essential to support transparent, accountable, and clean governance based on administrative law principles. Highlights • Licensing corruption reflects systemic violations of good governance principles through abuse of administrative authority• Administrative accountability remains weak due to limited integration between administrative and criminal legal frameworks• Strengthening supervisory institutions and digital licensing systems is central to clean and accountable governance Keywords General Principles Of Good Governance; Abuse Of Authority; Licensing Corruption; State Administrative Law; Administrative Enforcement